Mobile Government Applications Based on Security and Privacy: A Literature Review - Saeb Al-Sherideh, Ala'a; Ismail, Roesnita; Abdul Wahid, Fauziah; Fabil, Norasikin; Ismail, Waidah (International Journal of Engineering and Technology, 2018)
Mobile applications available in anytime and from anywhere. The utilizing of mobile governmental applications is significant to reduce the efforts and time that are required to accomplish the public services by citizens. The main challenges that face the acceptance and adoption of mobile governmental applications are the privacy and security issues. The users, who do not trust the security of mobile governmental applications, may reject the use of these applications which discourages the government to adopt the mobile services. This study focuses in investigating the security and privacy requirements of mobile government applications. Many related works are reviewed and discussed to understand the important security requirements of mobile government applications. The main results indicate that effective privacy and security of mobile government applications should be assured so as to enhance the level of adopting and using these applications. The security requirements involve many considerations such as the hardware characteristics, software characteristics, and communication characteristics. This article mainly gives better understanding of security requirements of mobile government applications.Â Â Â